Endodontic retreatment in the appealability structure of the compulsory medical insurance on the example of the state dental practice - E. V. Ivanova; E. G. Sabantseva; E. V. Petushkova (Эндодонтия Today, 2021)
Aim. To assess the need for repeated endodontic treatment and to determine the possible reasons for the repeated revision of the root canals according to the archival material of the state polyclinic in the period 2015-2020.Materials and methods. Archival data of the registry of the state polyclinic in the period from 2015 to 2020, containing information on repeated endodontic treatment, namely: data on the treatment of patients and the condition of their teeth with apical periodontitis on the admission of CHI, repeated revision of root canals, method and means of mechanical and drug treatment of canals, filling material before and after the revision of root canals, X- rays at all stages of treatment with their description. In accordance with the purpose of the study, descriptive statistics were carried out, the data that were obtained as a result of processing information on the material of the archive of the dental clinic were analyzed and described, absolute frequencies and their proportions were indicated, which are shown in the diagrams, it was done in the Microsoft Excel program.Results. In 505 teeth (54%), the root canals were obturated with resorcinol - formalin paste, most of the root canals of the teeth - 373 (40%) were sealed at half their length, on sighting radiographs in 80% of cases an expansion of the periodontal gap was revealed, in addition to destructive changes in bone tissue, basically all cases were treated under a temporary calcium- containing paste, 4% of the root canals of the teeth (35) were not obturated with permanent material, due to the absence of patients, 5 teeth (0.5%) underwent surgical treatment. Of all the cases identified, only 1% (10 cases of repeated endodontic treatment) have information about long-term results, which are positive.Conclusions. Thus, a complex of factors contributes to the occurrence of apical periodontitis, and the selection of one of them, as the main one, will not solve the problem of this complication. Dentists - therapists should focus their attention at each stage of primary and/or repeated endodontic treatment, adherence to the irrigation protocol, mechanical treatment of root canals, high- quality obturation, and most importantly, motivate patients to follow- up visits and control long-term treatment results through computed tomography and control sighting pictures.